AI and the future of work: investigating the transformation of the labor market in China's secondary sector with a focus on income distribution, skill gaps, and unemployment rates - Ishak, Suryati; Ren, Jingxuan; Hamzah, Hanny Zurina (Cuadernos De Economia, 2024)
This study looks at the relationship among Artificial Intelligence, unemployment, skill mismatches, and income distribution in China's secondary industry including manufacturing and construction concerns. For econometric modelling, a large dataset from China's National Bureau of Statistics covering the years 2000–2022 and industry reports are used. Machine learning approach and random forest regression are used to assess the adoption of AI and labor market indicators such as unemployment and income inequality. Openended questionnaires of a group of 50 employers and employees as well as focus group discussions emphasize the need for workplace adaptation, shifting skill needs, and the social effects of AI adoption. The findings suggest that high level of AI adoption are linked with overcome the income inequality as proved as Gini Coefficients are significant with AI integration. These quantitative studies indicate AI's impact on secondary sector income and employment. Qualitative thematic research shows how AI integration in the work market affects people. Focus groups and open-ended surveys emphasize AI adoptionrelated skill demands and workplace dynamics, including adaptation, lifelong learning, and technology adaption. The thematic analysis shows that creativity, critical thinking, and emotional intelligence improve AI and human-AI interactions. These qualitative results illuminate AI integration's social, organisational effects and emphasize workforce development and technology adaption. The study highlights the intricate interplay between technology and labor markets, underscoring the necessity of taking preemptive steps to capitalize on AI's advantages and avert its drawbacks in order to attain economic growth among automation.